Afterthoughts on colonoscopy. Was it that bad?. (June 2021) - Decruz, Glenn M; Ng, Cheng H; Lim, Kia T; Devi, M K; Lim, Frances; Tai, Chia H; Chong, Choon S
Objectives: Colorectal cancer is among the top three most common cancers globally. In order to reduce the health burden, it is important to improve the uptake of colorectal cancer screening by understanding the barriers and facilitators encountered. There are numerous reports in the literature on the views of the general public on cancer screening. However, the experiences of colonoscopy patients are not as well studied. This paper maps their perceptions. Methods: Keyword searches for terms such as 'colorectal', 'colonoscopy' and 'qualitative' were conducted on 3 December 2019 in five databases: Medline, Embase, CINAHL, PsycINFO and Web of Science Core Collection. Qualitative articles that quoted colonoscopy-experienced patients with no prior history of colorectal cancer were included for the thematic analysis. The systematic review was then synthesized according to PRISMA guidelines. Results: The major themes were distilled into three categories: pre-procedure, during and post-procedure. The factors identified in the pre-procedure phase include the troublesome bowel preparation, poor quality of information provided and the dynamics within a support network. Perceptions of pain, emotional discomfort and the role of providers mark the experience during the procedure. The receipt of results, opportunities given for discussion and finances relating to colonoscopy are important post-procedure events. Conclusion: Understanding colorectal cancer screening behaviour is fundamental for healthcare providers and authorities to develop system and personal level changes for the improvement of colorectal cancer screening services. The key areas include patient comfort, the use of clearer instructional aids and graphics, establishing good patient rapport, and the availability of individualized options for sedation and the procedure.